Role of the principal towards enhancing students academic achievement in the islamic private secondary schools, Thailand - Himphinit, Musakkid; Salleh, Mohamad Johdi (2011)
The main purpose of this study is to examine the roles of school principals as perceived by school teachers regarding the enhancement of students’ academic achievement. The study was conducted on 10 selected Islamic private secondary schools under Songkla Educational Service Office Area 3 in Thailand. The study employed the quantitative method used a set of questionnaire based on conceptual framework. Statistical analysis included descriptive approach, frequency, percentage and correlation. A survey instrument was distributed to 200 school teachers who were selected by simple random sampling. Findings of the study showed that school principals played their roles were moderately (leadership, managerial, and instructional – curriculum) that effect and affect to student performances in Ordinary National Test (O-NET) in particular subjects such as Mathematics and Sciences that scored lower than national standard as regarding to students’ academic achievement in this country.